Building B2B brands through advertising - Torlini, Fabio (Henry Stewart Talks, 2008)
Best B2B brand criteria, Considered purchase, The buying process, Neuropsychology, Heuristics, Left and right brain functions, Neuroeconomics, Brands establish an emotional connection, The resistance iceberg, Brand associations, The total brand experience, The move to experiential marketing, Rackspace: a case study, Our key differentiator, The Rackspace personality, Industry positioning, Living the brand
Archived at 2022/03/17